Percepção dos trabalhadores de saúde sobre a exposição a micro-organismos multirresistentes - Silva, Ludimila Cristina Souza (2013)
INTRODUCTION: Pediatric Intensive Care Unit ( UTIin ) is an unhealthy environment due to the performance of procedures and use of invasive devices , antimicrobial use, among others . This situation makes workers vulnerable to colonization by pathogens and potential backers health. Thus corroborate unconformities on the principles of patient safety and worker. OBJECTIVE: To analyze the perception of health workers related to occupational exposure by multiresistant microorganisms in a Pediatric Intensive Care Unit of an institution 's Health System of Goiania - Goias . METHODS: This was a descriptive, analytical research , qualitative in nature , performed in the Intensive Care Unit of an Institution of Child Health Health System in Goiânia -GO. The population consisted of 22 workers of the multidisciplinary health care team. Data collection occurred from June to August 2012, through interviews, individual, guided by a form previously analyzed by " expertise " consists of two parts. Objective questions were used to characterize the workers. Subjective divided into two parts, one for smoothing the knowledge about multidrug-resistant micro - organisms and risk / occupational exposure. And other two guiding, following the Critical Incident Technique (ICT). Data were organized and analyzed according to qualitative analysis of Bardin, Software Atlas ti and the four dimensions of the Health Belief Model proposed by Rosenstock. RESULTS: Regarding gender, all workers were women, aged 24 and 50, 11 (50.2%) were nurses. The training of 11 (50.2%) were graduate with training time ranging from 1 to 24 years. On the issue of qualification, 16 (72.7%) attended at least one training on biosafety and / or bacterial multidrug resistance to antimicrobial agents. Knowledge of these micro -organisms was reported by 14 (63.6%) workers. The Perceived Susceptibility category, according to the Health Belief Model proposed by Rosenstock, was endorsed by the "perceived risk of illness", "infection/contamination /colonization by micro -organisms "and" infection / cross contamination". Already Perceived Benefits were attributed to the "availability of Personal Protective Equipment", "continuing education", "proper physical structure","environmental hygiene","information","adequate human resources" and "ventilation in the room."The Perceived Barriers by "difficulty in preventing "and" lack of preventative measures." Situations involving occupational exposure to multidrug-resistant micro -organisms exposure yielded 41 critical incidents, of which 26 (63.4%) had negative polarity. These incidents were composed of 41 cases from which was obtained 59 behaviors. Of these, 35 (59.3%) was considered as positive analysis. When examined in the light of the consequences for workers, emerged 66 consequences, obtaining these, 35 (59.3%) with negative polarity. Content Analysis emerged from these incidents four categories: " Exhibition of professional", "Pro - activity for safety professional" , "organizational safety culture" and "behavioral influence “. It apprehends these categories that workers do not have clarity about behaviors insurance during the workday, evidenced by situations of risk of exposure to micro-organisms. CONCLUSION: It was demonstrated that health workers had not sensitized about job security . It is believed that this gap is due to the paucity of an organizational culture rooted in service, work process short of Brazilian guidelines . It is recommended to reevaluate human resources policy and investment in continuing education programs, aiming to promote and add value and knowledge to safe practice.